Effects of Liquorice Juice on the Pharmacokinetics of Esomeprazole - Rawan Karaki; Mohammad Hailat; Israa Al-Ani; Zainab Zakaraya; Lina N.Tamimi; Sina M. Matalqah; Rehan Al-Kasasbeh; Wael Abu Dayyih; Mohammed Hamad (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The HPLC-MS technique was tested and verified in this work to quantify esomeprazole in rat plasma samples. A rat investigation demonstrated that co-administration of a single dosage of liquorice juice had no effect on the pharmacokinetic characteristics of esomeprazole, however successive doses of liquorice juice raised the t1/2 and area under the curve of esomeprazole. After introducing liquorice juice into the stomach, the pharmacokinetics of esomeprazole was determined simultaneously by HPLC-MS. The absorption of esomeprazole was rapid; esomeprazole was detected in plasma from the first blood sampling time, and the peak plasma concentration for the esomeprazole-treated group with multiple doses of liquorice was reached one hour after oral administration. At the same time, peak plasma concentration was reached 30 min after oral administration for the esomeprazole-treated group with a single dose of liquorice or distilled water. The plasma concentrations of esomeprazole in the esomeprazole-treated group with single-dose liquorice were comparable to those with single-dose distilled water. The plasma concentrations of esomeprazole were higher in the esomeprazole treated group with multiple doses of liquorice than in the esomeprazole treated group with single-dose distilled water, resulting in a significantly higher AUC, 2.5 times, in the esomeprazole treated group with multiple doses of liquorice. This could be due to decreased metabolism of esomeprazole by multiple doses of liquorice. Since esomeprazole is metabolized in the liver mainly by CYP2C19 and liquorice is a moderate inhibitor of CYP2C19 in humans there was an inhibition of CYP2C19 at multiple doses of liquorice. The inhibited metabolism of esomeprazole by liquorice resulted in asignificantly higher Cmax, 1.5 times, and a significantly longer terminal half-life, 1.45 times, than in the control group. Therefore, multiple administration of liquorice could increase the esomeprazole effect since a single dose did not affect esomeprazole metabolism.